Post-endodontic treatment using composite resin cement and fiber post - Daniel Černý; Radek Mounajjed (LLC "Endo Press", 2021)
Adhesive post-endodontic treatment does not yet have a generally accepted clinical protocol. We perform this procedure in our clinical practice since 2006. We have developed a clinically successful protocol. Tissues and materials which relate to the the procedure are described following available research. Protocol is described in step-by-step.